2017
DOI: 10.1093/ndt/gfw462
|View full text |Cite
|
Sign up to set email alerts
|

Unacceptable human leucocyte antigens for organ offers in the era of organ shortage: influence on waiting time before kidney transplantation

Abstract: This study demonstrates that the assignment of UAGs decreases the transplant probability in both main Eurotransplant allocation programs because of insufficient compensatory mechanisms. At present, for immunized patients, a prolonged waiting time has to be weighed against the increased immunologic risk due to donor-specific antibodies not assigned as UAGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…This has already been addressed by Ziemann et al . [13], who found that the waiting time is extended by 1.3 weeks if the PRA value is increased by 1% within the regular allocation and prolonged by 5 weeks within ESP. The cPRA did not impact relisting but did affect retransplantation in our cox regression model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has already been addressed by Ziemann et al . [13], who found that the waiting time is extended by 1.3 weeks if the PRA value is increased by 1% within the regular allocation and prolonged by 5 weeks within ESP. The cPRA did not impact relisting but did affect retransplantation in our cox regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant candidates with prior graft loss are known to be highly sensitized and have more anti‐HLA antibodies, irrespective if they underwent allograft nephrectomy or only withdrawal of immunosuppression [11,12]. As a consequence, the fear comes that dnDSA lead to a higher number of unacceptable antigens, which might as a consequence lead to a longer waiting time [13]. But whether this causality between dnDSA and waiting time also considering Eurotransplant Acceptable Mismatch (AM) program in the case of retransplantation is true is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The average waiting time for dialysis patients to receive kidney grafts in Japan is 13 years, as opposed to the 4 to 6 years prevailing in most countries. 21 , 22 The number of recipients on a waiting list for KTx has been increasing. Therefore, DCD donors have become an accepted organ resource to alleviate the chronic shortage of kidney grafts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all patients were tested with a Luminex-based LABScreen Mixed bead assay (One Lambda; Thermo Fisher Scientific, Inc.). In step-by-step analysis, 29 the anti-HLA class I and/or II positive sera with positive were subsequently specified with LABScreen single-antigen bead assays (One Lambda; Thermo Fisher Scientific Inc.). All beads with normalized median fluorescence intensity (MFI) values higher than 1000 were considered to be positive for anti-HLA antibodies.…”
Section: Methodsmentioning
confidence: 99%